1989
DOI: 10.1128/aem.55.10.2431-2436.1989
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Nodulation Responses of Rhizobium meliloti to Water Stress Induced by Permeating and Nonpermeating Solutes

Abstract: Isolates of Rhizobium meliloti , representing antigenically distinct indigenous serogroups 31 and 17, were grown in yeast extract-mannitol broth (YEM) containing NaCl or polyethylene glycol (PEG) to provide external water potentials ranging from −0.15 to −1.5 MPa. Several differences were found between representatives of the two groups in their abilities to adapt to water stress induced by the nonpermeating solute PEG. At potentials below −0.5 MPa, strain 31 had a lower specific growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(32 citation statements)
references
References 44 publications
0
32
0
Order By: Relevance
“…Soil microbial communities are among the most complex, diverse, and important assemblages in the biosphere (Zhou et al, 2003) and soil moisture is a key factor for microbial activity, its biomass and diversity in soils especially in desert (Kieft, 2002), and soil moisture stress leads to severe impact on vital metabolic processes and growth. To mitigate such stresses in desert, the bacteria must maintain osmotic equilibrium across the membrane by forming desiccationresistant spores or cysts (Gould & Measures, 1977) or tolerating low water potential as vegetative cells (Busse & Bottomley, 1989).…”
Section: Isolation and Characterization Of Osmotolerant Bacteria Frommentioning
confidence: 99%
“…Soil microbial communities are among the most complex, diverse, and important assemblages in the biosphere (Zhou et al, 2003) and soil moisture is a key factor for microbial activity, its biomass and diversity in soils especially in desert (Kieft, 2002), and soil moisture stress leads to severe impact on vital metabolic processes and growth. To mitigate such stresses in desert, the bacteria must maintain osmotic equilibrium across the membrane by forming desiccationresistant spores or cysts (Gould & Measures, 1977) or tolerating low water potential as vegetative cells (Busse & Bottomley, 1989).…”
Section: Isolation and Characterization Of Osmotolerant Bacteria Frommentioning
confidence: 99%
“…Alteration of membrane composition (Boumahdi et al 2001) and membrane permeability (Bushby and Marshall 1977b) have been suggested as potential mechanisms. Effects of water potential on growth rate and cell morphology have been documented, as well (Salema et al 1982b;Busse and Bottomly 1989;Mary et al 1994). It has been suggested that increased production of extracellular polysaccharide (EPS) would increase desiccation tolerance (Deaker et al 2004), but there are mixed results on this issue (Bushby and Marshall 1977a;Cliquet and Catroux 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the imposition of any stress to rhizobia results in adaptive responses, which lead to changes in the regular metabolic processes that are then reflected in protein profiles. The tolerant rhizobia to osmotic stress accumulate the osmolytes, and changes their morphology and dehydration of cells (Buss and Bottomley, 1989). There was a good correlation between the tolerances to both stressors; strains that were halotolerant were in general also tolerant to PEG, suggesting that common osmoadaptation mechanisms were operating.…”
Section: Discussionmentioning
confidence: 93%